Preparation and characterization of 3-[(1H-1,2,4-triazole-3-ylimino)methyl]naphtalene-2-ol film at the platinum surface for selective voltammetric determination of dopamine in the presence of uric acid and ascorbic acid - (:unkn) unknown (WILEY, 2019)
A [(1H-1,2,4-triazole-3-ylimino)methyl]naphthalene-2-ol (TMN-2-ol) film modified platinum (Pt) electrode has been fabricated by the electrochemical oxidation in acetonitrile solution. The modified surface was characterized by electrochemical impedance spectroscopy (EIS), scanning electron microscope (SEM), and X-ray photoelectron spectroscopy (XPS). The prepared Pt electrode can be used as a functional interface to sensitive and selective determination of dopamine (DA) in the presence of uric acid (UA) and ascorbic acid (AA) by square wave voltammetry (SWV) method. The limit of detection (LOD) and limit of quantification (LOQ) of DA were 9.25 x 10(-8) and 2.78 x 10(-7) M, respectively. Linear range of DA was found to be between 3.95 x 10(-7) and 4.19 x 10(-6) M.
Keywords: characterization; coating; determination; dopamine; surface modification; GLASSY-CARBON ELECTRODE; SELF-ASSEMBLED MONOLAYER; ELECTROCHEMICAL PROPERTIES; SENSITIVE DETERMINATION; DIAZONIUM REDUCTION; COATED ELECTRODE; PASTE ELECTRODES; SINGLE-CRYSTAL; IMPEDANCE; ADSORPTION